The role of teachers in instilling religious character in children aged 5-6 years in kindergarten - Emilawati, Yati; Sumiadi, Raden; Mahendra, Juandra Prisma (Panicgogy International Journal, 2025)
This study aimed to understand the role of teachers as educators and guides in implanting the religious character of five-year-old children and to examine the impact of this on group B children at TK Fathunintention. The research employed data collection methods such as observation, interviews, and documentation, with the data analysis following the techniques outlined by Miles and Huberman, which involved data condensation, data display, and verification. The study found that teachers played a pivotal role in implanting religious values through the use of breeding methods, which proved effective in shaping the religious character of the children. The results showed that, through these practices, children became capable of performing wudhu independently, memorizing short verses, correctly executing prayer movements, memorizing daily prayers, and reciting greetings. These practices not only enhanced the children’s religious knowledge but also contributed to their moral development and spiritual growth. It was clear that the teachers’ methods created a nurturing environment for the development of religious character, where the children could practice and internalize religious teachings in a meaningful way. Based on these findings, it was recommended that other institutions adopt similar structured methods to foster religious character, ensuring the integration of religious values into the daily lives of young children. Further research was suggested to focus on the long-term impact of these educational approaches on the children’s moral and spiritual growth, as well as investigate the role of parental involvement in supporting religious education. Teacher training programs were recommended to enhance the educators' ability to implement religious character education effectively, with an emphasis on pedagogical strategies that encouraged the holistic development of children's religious identity, ensuring consistency in the implementation of these practices across educational settings.